Human Resources Development (HRD) Policy for the Public Health Sector - Malawi Government: Ministry of Health (Malawi Government, 2021)
In most cases, Human Resource Development (HRD) interventions in the Ministry are ad-hoc and not in light of ongoing work on the human resource requirements. Consequently the current HRD interventions have had limited impact in improving the quantity and quality of personnel needed to implement the Essential Health Package (EHP). In particular, the identification of training needs, the development of training priorities and plans lack systematic analysis and are not linked to public health service goals and objectives. In addition, the human resource planning system is extremely weak and the selection of candidates for training is often haphazard, with focus primarily centered towards the training of professional workers. Furthermore, the relevance of the training programs is not validated by informed monitoring and evaluation systems. To effectively address this situation and at the same time respond comprehensively to the changes and current challenges, the Ministry and its partners view continuous training and staff development as a powerful tool to respond to the problem. Hence, the development of this HRD Policy. The ultimate aim of this policy therefore is to improve staff performance and productivity by maintaining experienced, well trained, motivated and committed personnel with leading-edge skills at all times.